Exploring the potential of blockchain technology for modernizing voting systems in digital public administration - Kovtun Y. O. (НТУ «ДП», 2024)
As governments embrace digital transformation, blockchain technology has emerged as a promising tool, particularly in the realm of secure, transparent voting systems. Traditional voting methods, whether in-person or electronic, often face security vulnerabilities, logistical challenges, and trust issues among citizens.
Keywords: exploring the potential of blockchain technology; modernizing voting systems